Christian Schröder Praeconsul Gedanensis Natus MDCXXVI Denatus MDCCI. / S. Thomassin. - Thomassin, Simon (1655-1733) (1703)
Przedstawia portret w popiersiu w obramieniu architektonicznym Christiana Schroedera.